Psychological status of women with breast cancer during chemotherapy - Santos, Ana (2022)
A breast cancer diagnosis and corresponding treatments bring several consequences to women at many distinct levels, particularly on a psychological level with the fast change of their routines and even of their bodies. As such, it seems important to understand to what factors women attribute their psychological state during or shortly after chemotherapy. Therefore, it was carried out a qualitative cross-sectional study with the main objective: to comprehend which factors contribute to women’s psychological state, in their perception, during or shortly after the submission to chemotherapy. Twenty-five women with breast cancer submitted to neoadjuvant chemotherapy were recruited through a non-probabilistic convenience sampling method. Data were collected through a structured interview and were analysed using Grounded Theory. Ten categories women consider as factors that contribute to their psychological state were identified: diagnosis’ impact; treatment’s side effects; psychological symptoms; excessive information; general well-being; social support; personal characteristics; health care; and external factors to the disease. These results show that several factors affect women psychologically during chemotherapy: some negatively and others positively. We concluded that psychologists should give personalised attention to each patient to understand their needs for being more capable of promoting factors that positively contributed to these women psychological state.